Age and task type effects on comprehension and production of narrative macrostructure: storytelling and retelling by Swedish-speaking children aged 6 and 8 - Lindgren, Josefin (Frontiers in Communication, 2023)
It is often said that story retelling tasks, where children listen to a model story and then retell it, are easier than story telling tasks, where children are not provided with a model. However, previous studies have rarely used comparable stimuli and procedures for the different tasks, creating possible confounds with task effects. Additionally, studies seldom investigate the interaction between age and task type and most studies focus on preschool children. The present study addresses these gaps by analyzing the performance of Swedish-speaking 6-year-olds and 8-year-olds (N=74) on measures of story comprehension and story structure (narrative macrostructure) using a carefully controlled procedure with comparable telling and retelling tasks (MAIN Cat/Dog stories) and counterbalancing the order of the tasks. For story comprehension, results showed that overall accuracy was uniformly high (>90%) across tasks and age groups. However, performance was substantially lower for one question (D10), that assesses comprehension of the entire plotline. With increasing age, children did not become more likely to answer this question correctly, nor did hearing a model story improve performance. A qualitative analysis showed that incorrect answers often contained reasonable explanations showing advanced general inferencing abilities. In light of these results, an adjustment to the scoring of MAIN is recommended. For story structure, results showed significant effects of both age and task type, with higher scores in retelling and higher scores by the 8-year-olds. The 8-year-olds exhibited the same performance gap between telling and retelling as the 6-year-olds. There was also a significant effect of task order, showing a training effect from the first task to the second. The present study thus confirms previous findings that expressing story structure in a retelling task is easier than in a telling task, but showing this for the first time while controlling for task order and stimulus complexity in MAIN.